Characteristics and assessment of stress management workshop for psoriasis patients - Miniszewska, Joanna; Chanduszko-Salska, Jolanta; Ograczyk, Alicja; Zalewska, Anna (Current Problems of Psychiatry, 2015)
Psoriasis is one of the so-called psychodermatological diseases. It can give rise to a range of psychological problems in affected individuals, like high stress level, low self-esteem, altered body image, and affective disorders (like depression or social anxiety). On the other hand, psoriasis is caused, triggered, or exacerbated by a range of difficulties, including psychological stress. Therefore, the holistic approach to cutaneous diseases is pointed out in modern psychodermatology. Aim: The aim of the article is to present the characteristics and principles of coping-with-stress workshop for patients with psoriasis and show its evaluation made by the participants. Material and methods: The study comprised 62 participants with the diagnosis of psoriasis vulgaris. They participated in stress management workshops conducted in four cities. The PSS-10 and scaling method were used to assess patients’ stress level during the training sessions. Results: During the training sessions, the stress level in patients was decreasing regularly. Patients pointed to the need of training courses that are more psychological in nature and having a meeting with a dermatologist for getting information about the treatment of the disease and skin care. Conclusions: Participation in psychological workshops dedicated to psoriasis and arranging extra meetings with doctors may be important for mental health of psoriasis patients.